Analysis of Factors Associated with The Occurrence of Anemia in Adolescent Girls in Indonesia - Purwanto, Edi; Dhiyaulhaq, Faradhifa Shafahana (Jurnal Keperawatan, 2024)
The main causes of anemia are a lack of knowledge about anemia, lack of iron, vitamin 12, vitamin A, and folic acid. The aim of this research was to find out what factors are associated with the incidence of anemia in adolescent girls in Indonesia. This research is an analytical survey using a cross-sectional design. The population in this study was women aged 19-25 years. Data was collected using secondary data from the 2017 Indonesian Demographic Health Survey (SDKI) and analyzed using the SPSS Paired T-Test. The results of this research are the occurrence of anemia in women in Indonesia, which is related to age, gender, education level, occupation, case criteria, drug consumption, and distance from home.